Perbandingan Aktivitas Ekstrak Daun Tapak Dara (Catharanthus Roseus) dan TBHQ Sebagai Antioksidan Minyak Goreng Terhadap Fotooksidasi UV-C - Akhmad Al-Bari; Romadhiyana Kisno Saputri (Al-Kimia, 2021)
Cooking oil is one of the sources of human energy with a total consumption of 290 million tons/year by the public. The largest use of cooking oil is the household sector which generally gets its oil from traditional markets. The oil that is traded in the market is often not covered properly so that it is easily exposed to sunlight. The light that hits the oil can cause damage, including the formation of peroxide compounds. Efforts to overcome the damage include adding natural antioxidants as an alternative to synthetic antioxidants. This study aims to determine the impact of 254nm ultraviolet photooxidation on the containment of oil oxidation by the addition of tapak Dara leaf extract and TBHQ. The oil was photo oxidized with variations of 1, 3, 6, and 12 hours to determine the hold. To determine the quality of the oil, three parameters of sample testing were carried out, namely free fatty acid content, peroxide number, and water content. The results of photooxidation showed that cooking oil with tapak Dara leaf extract had lower holding activity than TBHQ. This value was measured on the peroxide number and free fatty acid content, while the measurement of the water content of the measured containment activity was better with a value that met SNI, namely <0.1%